RISK FACTORS FOR DEVELOPING TYPE 2 DIABETES MELLITUS - Ergasheva Gulshan Tokhirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Diabetes mellitus (DM) is a group of metabolic diseases characterized by chronic hyperglycemia, which results from impaired insulin secretion, insulin action, or both. Chronic hyperglycemia in diabetes is accompanied by damage, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, heart and blood vessels. Diabetes mellitus type 2 (DM 2) is a disorder of carbohydrate metabolism caused by predominant insulin resistance and relative insulin deficiency or a predominant disorder of insulin secretion with or without insulin resistance.